A vital role for myosin-9 in puromycin aminonucleoside-induced podocyte injury by affecting actin cytoskeleton. (2nd June 2016) - Yuan, Yanggang; Zhao, Chuanyan; An, Xiaofei; Wu, Lin; Wang, Hui; Zhao, Min; Bai, Mi; Duan, Suyan; Zhang, Bo; Zhang, Aihua; Xing, Changying
ABSTRACT: Podocyte injury is an early pathological change of many kidney diseases. In particular, the actin cytoskeleton plays an important role in maintaining the normal function of podocytes. Disruption of the actin cytoskeleton is a feature of podocyte injury in proteinuric nephropathies. Recent studies showed that myosin-9 was localized in the podocyte foot processes and was necessary in maintaining podocyte structural homeostasis. However, it is unclear whether myosin-9 maintains podocyte structure by affecting actin cytoskleton. Here, the role of myosin-9 in puromycin aminonucleoside (PAN)-induced podocyte injury was explored both in vitro and in vivo . In cultured mouse podocytes (MPC5), it was determined that PAN downregulated myosin-9 expression, disrupted the actin cytoskeleton and reduced the adhesion ability. Reduced myosin-9 expression by siRNA precipitated podocyte cytoskeletal damage and accelerated PAN-induced podocyte detachment. Overexpression of myosin-9 protected against PAN-induced podocyte detachment. Furthermore, administration of an antioxidant Mn(III)tetrakis (4-benzoic acid) porphyrin (MnTBAP) inhibited PAN-induced podocyte cytoskeletal damage and podocyte detachment by restoring the expression of myosin-9. In the rat PAN nephropathy model, MnTBAP could also attenuate PAN-induced reduction of myosin-9 and podocyte loss. Taken together, these findings pinpointed that oxidative stress contributed to PAN-induced podocyte injury through the repression of a cytoskeletal protein myosin-9, which provided novel insights into a potential target for the treatment of podocyte injury-associated glomerulopathies.